A single-arm feasibility study of community-delivered Baduanjin (Qigong practice of the eight Brocades) training for frail older adults - Liu, Xiao (Pilot Feasibility Stud, 2020)
BACKGROUND: Frailty is a common geriatric syndrome, characterized by reduced physiologic reserve and increased vulnerability to stressors, due to cumulative decline in multiple physiological systems. We studied the feasibility of a community-delivered Baduanjin (BDJ) training program among pre-frail/frail community-dwelling older people. We examined (1) safety (adverse events) and physical and psychological effects; and (2) feasibility of recruitment, retention, adherence; recruitment efforts, and any program challenges, so as to inform future studies. METHODS: Our study was a single arm pre-post study in a community setting. Sixteen-week group BDJ training (2×/week in the first 4 weeks and 3×/week thereafter) was co-designed and implemented by community-based providers in Singapore. Recruitment, attendance, and adverse events were recorded throughout the training. A participants’ survey was also administered after the training program. Effects of the intervention on physical and functional outcomes (hand grip strength, knee extension strength, Time Up and Go (TUG), Physiological Profile Assessment (PPA), 30-s Sit-to-Stand test, 6-m fast gait speed test), frailty outcomes (frailty score and status), and other outcomes (Maastricht Questionnaire (MQ), Fall Efficacy Scale (FES), Montreal Cognitive Assessment (MoCA), Geriatric Depression Scale (GDS), and EQ-5D-5L) were examined before and after the program. RESULTS: Of 31 older adults screened to be frail, 15 met inclusion criteria and 3 refused participation, resulting in 12 older adults (9 women) enrolled into the program. During the program, one participant was hospitalized (unrelated to BDJ training) and the other 11 (aged 77 ± 6 years; 2 frail, 9 prefrail at baseline) completed the program with average overall attendance of 89%. Most (89%) of the 44 training sessions had attendance > 80%. The program received positive feedback with no training-related adverse events. Participants either reversed (n = 2) or maintained (n = 9) their frailty statuses. There post-training outcomes in hand grip strength, knee extension strength, TUG, MQ, FES, MoCA, GDS, and EQ-5D-5L index score appeared to be better. The reduction of frailty and PPA fall risk scores was of moderate-to-large effect size. CONCLUSIONS: Community-delivered BDJ training program was safe and feasible for prefrail/frail older adults with the potential to improve physical and cognitive function, reduce fall risk, improve psychological well-being, and reverse frailty status.